Developing a Web-Based Information System for Nature Tourism Travel Packages in Southeast Aceh - Aidul Safii; Juniana Husna; Murniati (STMIK Methodist Binjai, 2026)
Southeast Aceh Regency is one of the regencies in Aceh Province that has many attractive natural tourism destinations, but information about these destinations is still very limited and not easily accessible to the general public. Information dissemination that is still carried out conventionally, such as through word of mouth, magazines, and flyers, causes tourism potential not to develop optimally. This study aims to design and build a Web-Based Nature Recreation Travel Package Information System in Southeast Aceh that can facilitate the public in accessing natural tourism information while making online travel package reservations. The development method used is the waterfall method which includes the stages of requirement, software design, implementation, integration, and maintenance. The system was built using PHP, HTML, CSS, Bootstrap framework, MySQL database, as well as Visual Studio Code and Sublime Text editors. The developed system features a home page with a list of tourist destinations, travel package pages, hotels, souvenirs, contacts, user login and registration, package ordering, payment proof upload, ticket printing, and an admin dashboard to manage all content. The results show that this web-based information system successfully presents comprehensive natural tourism destination information from Southeast Aceh and allows users to make online travel package reservations, thereby increasing accessibility for tourists and potentially improving the local economy.